Statistical pocket book of the German Democratic Republic - Germany (East). (Berlin : Staatsverlag der Deutschen Demokratischen Republik, 1987)
"The tables ... are excerpts from the comprehensive 'Statistical yearbook of the German Democratic Republic.'"
oo 22/01/2019
Ref.
Keywords: Statistics; Germany (East)